2016
DOI: 10.1126/science.aad7297
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope rupture and repair during cancer cell migration

Abstract: During cancer metastasis, tumor cells penetrate tissues through tight interstitial spaces, requiring extensive deformation of the cell and its nucleus. Here, we investigated tumor cell migration in confining microenvironments in vitro and in vivo. Nuclear deformation caused localized loss of nuclear envelope (NE) integrity, which led to the uncontrolled exchange of nucleo-cytoplasmic content, herniation of chromatin across the NE, and DNA damage. The incidence of NE rupture increased with cell confinement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

112
1,570
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 1,113 publications
(1,751 citation statements)
references
References 44 publications
112
1,570
4
2
Order By: Relevance
“…Cells migrate along a chemotactic gradient, and nuclear deformation is observed by time-lapse imaging of fluorescently labeled histones. As decribed previously, NE rupture was detected by monitoring the transient escape of green fluorescent protein (GFP) fused with a nuclear localization signal (NLS-GFP) from the nucleus into the cytoplasm and fluorescently labeled cytoplasmic DNA-binding protein (cGAS-RFP) that accumulates at newly exposed genomic DNA was used to monitor the sites of NE rupture (13). Cells were generated by stable expression of fluorescent reporter proteins, i.e., NLS-GFP and cGAS-RFP, by lentiviral transduction.…”
Section: Microfluidic Device and Ne Rupture Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells migrate along a chemotactic gradient, and nuclear deformation is observed by time-lapse imaging of fluorescently labeled histones. As decribed previously, NE rupture was detected by monitoring the transient escape of green fluorescent protein (GFP) fused with a nuclear localization signal (NLS-GFP) from the nucleus into the cytoplasm and fluorescently labeled cytoplasmic DNA-binding protein (cGAS-RFP) that accumulates at newly exposed genomic DNA was used to monitor the sites of NE rupture (13). Cells were generated by stable expression of fluorescent reporter proteins, i.e., NLS-GFP and cGAS-RFP, by lentiviral transduction.…”
Section: Microfluidic Device and Ne Rupture Experimentsmentioning
confidence: 99%
“…Recently it has been shown that rupture of the NE during cell migration through rigid constrictions can potentially lead to herniation of chromatin across the NE and breaking of DNA double strands (12,13). The rupture and blebs are often found at defective sites in the NE where the nuclear lamina signal was weak or absent (13).…”
Section: Prediction Of Lamina Buckling and Rupturementioning
confidence: 99%
See 1 more Smart Citation
“…Such movements also occur during cancer metastasis when tumor cells crawl through tight spaces possibly resulting in severe distortion of the cell nucleus (1). For these reasons a number of studies have focused on elucidating the mechanical properties of the nucleus, which is possibly the stiffest organelle in the cell.…”
mentioning
confidence: 99%
“…A few that come to mind are: (1) What is the mechanism underlying the maintenance of integrity of stretched DNA even on timescales of minutes? (2) Can one go beyond the scaling picture to describe the consequences of crowding in a deformed nucleus?…”
mentioning
confidence: 99%